The Impact of Jambi Malay Interference on Arabic Language Students in Indonesia - Abdul Muid; Salman Jufri; Salman Hasani (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This study aimed to investigate the impact of Jambi Malay language interference on communication in Arabic. This study used a descriptive-analytical approach and combined corpus analysis methods, interviews, and observations to collect relevant data. The participants of the study were Jambi Malay speakers, in this case, the students of Pondok Pesantren Modern Darussalam Gontor 10 Muara Sabak Jambi, who used Arabic in daily communication. The results showed that interference of Jambi Malay affected Arabic communication in several aspects. Regarding phonology, differences are found in pronouncing certain Arabic sounds, which can lead to inaccuracies and misunderstandings in using Arabic. In terms of vocabulary, this interference results in the use of loan words or meaning adaptation of Arabic words in Jambi Malay, causing changes in the meaning and misuse of words in Arabic communication. Jambi Malay sentence patterns, such as the placement of subjects at the end of sentences, affect how sentences are arranged in Arabic and cause discrepancies with correct Arabic grammar. Interference is also seen in using different conjunctions and connecting words between Jambi Malay and Arabic. This study provides an in-depth understanding of the impact of Jambi Malay interference on Arabic communication.